Substratos renováveis na produção de mudas de Tectona grandis Linn F. - Trazzi, Paulo André (2011)
Industrial, urban or agro-industrial waste can be used as a source of nutrients to contribute to the reduction of production costs of forest seedlings. This study aimed to evaluate the use of biosolids and animal manure as a substrate component in the production of seedlings of Tectona grandis. Seedlings were produced in tubes with a volume capacity of 280 cm³, filled with two groups of waste, representing two studies. The first was to formulate substrates with biosolids (BIO) associated with rice hulls (CAC) or shredded coconut fiber (CF) in proportions 80:20, 60:40, 40:60, 20:80 (v: v), and also with 100% BIO forming nine treatments based on BIO submitted to the comparison of treatment with the commercial forest substrate. The second study was characterized for using proportions (v: v: v) of 15, 25 or 35% of cattle manure (EB), poultry litter (CF) or quail manure (EC) associated with the subsoil earth (60, 50 or 40%, respectively) and to 25% of commercial forest substrate (fixed volume), forming a set of nine treatments that were compared to treatment with commercial growing forest. Substrates formed of these treatments were subjected to chemical and physical analysis. Seedlings were evaluated for morphological characteristics ninety days after transplanting. To evaluate nutritionally the seedlings, the shoot was subjected to chemical analysis. The results of physical analysis showed that the CAC or the FC associated with BIO provided an increase in total volume of pores (VTP) and reduction in apparent density (DENS). The CAC promoted an increase in macroporosity (MAC), while the FC increased the microporosity (MIC). The use of animal waste increased the VTP, the MAC and the MIC and decreased the DENS. For chemical analysis, substrates formulated with BIO showed high levels of total and available nutrients. The manure of animals promoted an increase in the content of total and available substrates, especially P and K. Considering the content and accumulation of nutrients, the higher were obtained in treatment with 80% of BIO + 20% of CAC for the treatments with biosolids. For the study with the animal manures, the largest accumulation of nutrients was observed in the treatment with 35% of CF. The BIO with 60 and 80% associated with CAC and FC promoted greater gains in height, diameter, dry mass of shoot and root, in the experiment with biosolids. The seedlings produced with animal manures had the highest growth in substrates formulated with CF. The utilization of renewable substrates contributed to the improvement of physical and chemical characteristics of formed substrates and consequently in the nutrition of seedlings and therefore may be suitable for production of forest seedlings